PENYESUAIAN PELAKSANAAN PERKAWINAN DI KANTOR URUSAN AGAMA PADA MASA PANDEMI COVID-19 - Azhari, Ari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The orientation of this research is how the implementation adjustment of marriage during the Covid-19 pandemic to PMA RI No. 20 of 2019 concerning registration of marriages. This study applies a qualitative paradigm. This research also includes library research with documents as the main data source. The research results show that the procedure for registering marriages has been regulated in it. The stages or procedures are: registration of the will of marriage, examination of the will of marriage, announcement of the will of marriage, contract of marriage, and implementation of registration of marriages. This aims to prevent and reduce the risk of the spread of the Covid-19 outbreak and protect KUA employees and the public at the time of the marriage contract while adhering to very strict health protocols.